(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
St. Teresa of Jesús is one of the best-known authors of Spanish mystical literature. But despite the amount of scholarship on her writing, the influence that the Devil exercises on St. Teresa in her autobiographical account of her journey toward self-knowledge has scarcely been explored. In her difficult battles with him, she manages to face, control and overcome the Devil before surrendering her soul to mystical union with God. In this article, I propose to examine the ways in which Satan appears to St. Teresa of Jesús, making the distinction between what were considered actual mystical experiences, and those that were extraordinary—but not mystical—phenomena.